Exogenous application of l‐histidine suppresses bacterial diseases and enhances ethylene production in rice seedlings. (20th May 2019) - Yariyama, S.; Ando, S.; Seo, S.; Nakaho, K.; Miyashita, S.; Kanayama, Y.; Takahashi, H.
Abstract : Exogenous application of l ‐histidine enhances resistance to pathogens in tomato ( Solanum lycopersicum ) and Arabidopsis thaliana via activation of the ethylene (ET)‐dependent signalling pathway. In this study, the efficacy of l ‐histidine for suppression of bacterial diseases in rice seedlings was investigated. Rice seeds were soaked in 10 mm l ‐histidine, 10 mm l ‐lysine, or distilled water (DW) as a control for 48 h at 28 °C to stimulate germination. Treated seeds were then vacuum‐inoculated with Burkholderia glumae or B. plantarii . Seedling diseases caused by both of these bacterial pathogens were suppressed by treatment with l ‐histidine but not by treatment with l ‐lysine or DW. Expression of an ET‐responsive defence‐related gene, OsGLP8‐12, was induced by treatment of seeds with l ‐histidine. As diseases were not suppressed in rice seedlings treated with l ‐histidine after vacuum‐inoculation, pretreatment of rice seedlings with l ‐histidine before inoculation might activate the plant immune system. Indeed, ethylene production and the abundance of 1‐aminocyclopropane‐1‐carboxylic acid (ACC) synthase 2 ( OsACS2 ) transcript increased in healthy seedlings grown from rice seeds treated with l ‐histidine but not in those treated with DW. Furthermore, treatment of rice seeds with ACC, an ethylene precursor, suppressed bacterial rice seedling rot caused by B. glumae as effectively as did treatment with l ‐histidine, whereas treatment of rice seeds with aminooxyacetic acid, an inhibitor of ACC synthase, partially compromised disease suppression. Taken together, l ‐histidine seems to suppress bacterial rice seedling diseases via an ethylene‐dependent resistance pathway.